Gene Expression Profiles Normalized in Psoriatic Skin by Treatment with Brodalumab, a Human Anti–IL-17 Receptor Monoclonal Antibody - Russell, Chris B; Rand, Hugh; Bigler, Jeannette; Kerkof, Keith; Timour, Martin; Bautista, Edgar; Krueger, James G; Salinger, David H; Welcher, Andrew A; Martin, David A (The Journal of immunology (1950), 2014)
The IL-17 pathway is an established driver of psoriasis pathogenesis. We examined the detailed molecular and cellular effects of blockade of IL-17 signaling in human psoriatic skin before and following treatment with brodalumab, a competitive inhibitor of the IL-17 Receptor A subunit. Thousands of aberrantly expressed genes in lesional skin normalized within 2 weeks following brodalumab treatment, with conversion of the lesional psoriasis transcriptome to resemble that seen in nonlesional skin. Keratinocyte-expressed genes appeared to normalize rapidly, whereas T cell–specific normalization occurred over six weeks. The three IL-17 ligand genes that are upregulated in lesional skin, IL17A, IL17C, and IL17F, were all downregulated in a dose-dependent manner following brodalumab treatment. Cellular measures also showed a similar pattern with dramatic decreases in keratinocyte hyperplasia within one week, and decreases in infiltrating leukocytes occurred over a longer timescale. Individuals with the highest brodalumab exposure showed normalization of both IL-17–responsive genes and the psoriasis transcriptome, whereas subjects with lower exposures showed transient or incomplete molecular responses. Clinical and molecular response appeared dependent on the extent of brodalumab exposure relative to the expression of IL-17 ligand genes, and reduction of IL-17 signaling into the nonlesional range was strongly correlated with normalization of the psoriasis transcriptome. These data indicate that blockade of IL-17 signaling in psoriatic skin leads to rapid transcriptomal changes initially in keratinocyte-expressed genes, followed by normalization in the leukocyte abnormalities, and demonstrates the essential role of the IL-17R on keratinocytes in driving disease pathogenesis.